Immune responses during COVID-19 breakthrough cases in vaccinated children and adolescents - Daniela Rivera-Pérez; Daniela Rivera-Pérez; Constanza Méndez; Constanza Méndez; Benjamín Diethelm-Varela; Benjamín Diethelm-Varela; Felipe Melo-González; Felipe Melo-González; Felipe Melo-González; Yaneisi Vázquez; Yaneisi Vázquez; Xing Meng; et al. (Frontiers in Immunology, 2024)
BackgroundVaccine effectiveness against SARS-CoV-2 infection has been somewhat limited due to the widespread dissemination of the Omicron variant, its subvariants, and the immune response dynamics of the naturally infected with the virus.MethodsTwelve subjects between 3-17 years old (yo), vaccinated with two doses of CoronaVac®, were followed and diagnosed as breakthrough cases starting 14 days after receiving the second dose. Total IgGs against different SARS-CoV-2 proteins and the neutralizing capacity of these antibodies after infection were measured in plasma. The activation of CD4+ and CD8+ T cells was evaluated in peripheral blood mononuclear cells stimulated with peptides derived from the proteins from the wild-type (WT) virus and Omicron subvariants by flow cytometry, as well as different cytokines secretion by a Multiplex assay.Results2 to 8 weeks post-infection, compared to 4 weeks after 2nd dose of vaccine, there was a 146.5-fold increase in neutralizing antibody titers against Omicron and a 38.7-fold increase against WT SARS-CoV-2. Subjects showed an increase in total IgG levels against the S1, N, M, and NSP8 proteins of the WT virus. Activated CD4+ T cells showed a significant increase in response to the BA.2 subvariant (p<0.001). Finally, the secretion of IL-2 and IFN-γ cytokines showed a discreet decrease trend after infection in some subjects.ConclusionSARS-CoV-2 infection in the pediatric population vaccinated with an inactivated SARS-CoV-2 vaccine produced an increase in neutralizing antibodies against Omicron and increased specific IgG antibodies for different SARS-CoV-2 proteins. CD4+ T cell activation was also increased, suggesting a conserved cellular response against the Omicron subvariants, whereas Th1-type cytokine secretion tended to decrease.Clinical Trial Registrationclinicaltrials.gov #NCT04992260